Considering musical communities online and offline: A dedication to the life and work of Janice Waldron (13 April 1957–7 November 2022). Issue 1 (1st March 2023) - Mantie, Roger; Bayley, Jonathan; Veblen, Kari; Allstaff, Kirsten; Sirek, Danielle
Janice Waldron (1957–2022), professor at the University of Windsor (Canada), was an accomplished musician, teacher and researcher. Her scholarly passions revolved around informal music learning practices, online and offline music communities, social media and music learning, and Irish and Scottish traditional musics. In this dedication to Waldron, five friends and colleagues – Kari Veblen, Jonathan Bayley, Kirsten Allstaff, Danielle Sirek and Roger Mantie – offer reflections on her life and work and the legacy she has left for scholars and practitioners of community music.